GROWTH ASSESSMENT OF SPINY LOBSTER (PANULIRUS HOMARUS) UNDER OPEN SEA CAGE CULTURE IN THARUVAIKULAM OF TAMIL NADU COAST, SOUTH INDIA - S. ATHITHAN; A. GOPAL AKANNAN (The Bioscan, 2015)
Suspended floating open sea cage for the aquaculture of juvenile spiny lobsters, Panulirus homarus was assessed at Tharuvaikulam village of Tamil Nadu coast, India. Juvenile lobsters were grown for 101 days and regularly fed with live clam (Donax sp) as natural feed. Juvenile lobsters with average weight of 75.75 g in the cage grew to an average weight of 104.50 g in 101 days with average wet weight gain and survival rate of 28.75g and 88.50 % respectively. The mean weight gain showed highly significant (p<0.001) positive relationships with culture period. The mean growth values showed no significant difference between the cages. The present study suggests that floating open sea cage culture gave better growth for under sized spiny lobsters by fattening method.